APREMILAST: AN UPDATE ON ITS EFFICACY AND SAFETY DURING LONG-TERM TREATMENT OF PATIENTS WITH PSORIATIC ARTHRITIS - Yu. L. Korsakova; T. V. Korotaeva (Научно-практическая ревматология)
Psoriasis (PS) is a chronic inflammatory disease of the skin; its prevalence in the world is 1 to 3%. Psoriatic arthritis (PsA) is a chronic inflammatory disease from a group of spondylarthritides (SpA) associated with PS, which is characterized by various manifestations: peripheral arthritis, enthesitis, dactylitis, spondylitis, and nail involvement. Therapy for enthesitis and dactylitis in PsA is a difficult task in clinical practice. The efficacy and safety of apremilast (APR), a tableted phosphodiesterase 4 inhibitor, have been demonstrated in the treatment of patients with active PsA in four phase III PALACE (Psoriatic Arthritis Long-term Assessment of Clinical Efficacy) placebo-controlled studies evaluating its long-term clinical efficacy and safety in PsA. The investigators analyzed the efficacy and safety of long-term APR treatment, in which 1493 patients received therapy with this drug for 260 weeks during the randomized clinical trials (RCTs) of PALACE 1–3: a placebo (PL) group consisted of 495 patients; a twice-daily APR 30 mg group included 497 patients, and twice-daily APR 20 mg group comprised 500 patients.At week 260, the percentage of patients who met the American College of Rheumatology (ACR) response criteria for 20%, 50%, and 70% improvement (ACR20, ACR50, and 70% ACR) with APR 30 mg twice daily were 67.2, 44.4, and 27.4%, respectively. The data of 208-week PALACE 4 showed that among 250 PsA patients, the percentage of those who met the ACR20, ACR50, and ACR70 were 68.2, 43.4, and 23.1%, respectively. The ACTIVE RCTs demonstrated that the effect of APR therapy in patients with PsA, which earlier had not received biological agents, was observed just at week 2, and then the efficiency of therapy increased at 52 weeks of treatment. After 52 weeks of taking APR 30 mg twice a day, the ACR20, ACR50 and ACR70 response rates were 67.1; 36.7% and 21.3%, respectively. The data of PALACE 1, 2, and 3 during a 156-week follow-up that reflected the effect of APR on enthesitis and dactylitis at 24 weeks of treatment with APR 30 mg twice daily indicated that there was a more pronounced reduction in the MASES index (-1.3 vs -0.9; p<0.05) and dactylitis scores (-1.8 vs -1.3; p<0.01) compared to PL. Among the patients treated with APR 30 mg twice daily for 24 weeks, the proportion of patients, in whom the enthesitis index reached zero, was significantly higher than in the PL group. At week 24 in the twice-daily APR 30 mg group, the mean dactylitis scores decreased significantly compared to baseline and to that in the PL group (p ≤ 0.01). Thus, APR, a new targeted synthetic disease-modifying antirheumatic drug (DMARD), a phosphodiesterase 4 inhibitor, is an effective agent that alleviates the manifestations of PsA and PS. This drug has a favorable safety profile and can be used alone and in combination with DMARD.